(untitled) (El-Wahat Journal for Research and Studies, 2025)
Political geography is the mirror that reflects the policy of international units, as rational and irrational external orientations and decisions are imposed on it. The Russian-Ukrainian war is one of the highest examples of the impact of geopolitical thought on the minds and perceptions of decision-makers. We find the federal state of Russia looking to restore its natural extension and its usurped heritage, and defend its national security and its outlet towards warm waters on the one hand. On the other hand, we find the state of Ukraine looking for a way to protect its borders in the face of the impasse imposed on it by its geography, as it has become an arena for competition and collision of the interests of the major powers, a focal point for Russia’s national security, and a pressure card in the hands of the Western alliance. On this basis, we decided to shed light on the war in Ukraine from a geopolitical perspective and put forward possible perceptions and scenarios about the region in general and the future of the Russian Federation in particular. Keywords: geopolitics; United Russia; Ukraine; the war; security; defense